Weaning from Venovenous Mode Extracorporeal Membrane Oxygenation in Coronavirus Disease 2019-Related Respiratory Distress Syndrome - Chih-Hsi Pan; Chung-Kan Peng; Chen-Liang Tsai; Chih-Hao-Shen (Journal of Medical Sciences, 2024)
The coronavirus disease-2019 (COVID-19) has caused a worldwide pandemic. Approximately 5% of victims develop severe acute respiratory distress syndrome (ARDS), and some require extracorporeal membrane oxygenation (ECMO). However, weaning patients with COVID-19-related ARDS from ECMO are challenging. Here, we report a COVID-19 case with severe ARDS that received venovenous ECMO to maintain adequate gas exchange for more than 4 weeks. We performed prolonged prone position ventilation and airway pressure release ventilation, and the patient was successfully weaned off ECMO.